2021
DOI: 10.1002/anie.202017320
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Nonribosomal Peptides Modulate Collective Behavior in Pseudovibrio Bacteria Isolated from Marine Sponges**

Abstract: Although swarming motility and biofilms are opposed collective behaviors, both contribute to bacterial survival and host colonization. Pseudovibrio bacteria have attracted attention because they are part of the microbiome of healthy marine sponges. Two‐thirds of Pseudovibrio genomes contain a member of a nonribosomal peptide synthetase‐polyketide synthase gene cluster family, which is also found sporadically in Pseudomonas pathogens of insects and plants. After developing reverse genetics for Pseudovibrio, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(41 citation statements)
references
References 47 publications
(79 reference statements)
4
33
0
1
Order By: Relevance
“…In the conceivable biosynthetic scheme for 1 , the BulbA NRPS would furnish the ureido linked Phe‐Leu dipeptide, as is consistent with prior reports of ureido bond construction in NRPS‐derived natural products, [9b,14] followed by canonical elongation of the peptide chain with Trp, Ile, Arg, and Leu residues. The organization of the BulbD and BulbE NRPSs is curious.…”
Section: Resultssupporting
confidence: 82%
“…In the conceivable biosynthetic scheme for 1 , the BulbA NRPS would furnish the ureido linked Phe‐Leu dipeptide, as is consistent with prior reports of ureido bond construction in NRPS‐derived natural products, [9b,14] followed by canonical elongation of the peptide chain with Trp, Ile, Arg, and Leu residues. The organization of the BulbD and BulbE NRPSs is curious.…”
Section: Resultssupporting
confidence: 82%
“…The majority of bacteria isolated in this study could be assigned to the Gram-negative proteobacterial Pseudovibrio , Ruegeria , and Microbulbifer genera ( Figure 2 ). All three genera have extensive literature precedents for association with marine invertebrates and are well validated sources of bioactive natural products [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Recently, a Pseudovibrio isolate from a Verongid sponge was reported to produce bromotyrosine alkaloid natural products [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…A combination of MS imaging and biology experiments showed that this new class of non-surfactant heptapeptides was excreted, promoting motility, and reducing biolm formation. 28 Genome mining of a Saccharothrix strain led to the identi-cation of a type II PKS BGC (sxn), that encoded several distinct subclasses of oxidoreductases, leading the researchers to hypothesise that this strain had the potential to produce novel polycyclic aromatic polyketides with unusual redox modications. Application of the One Strain Many Compounds (OSMAC) strategy using this marine bacterium and comparative metabolite analysis facilitated the discovery of 20 angucycline derivatives including six new highly oxygenated aromatic polyketides and four new glycosylated derivatives named saccharothrixins D-I 83-88 and saccharothrixins J-M 89-92, respectively.…”
Section: Marine-sourced Bacteriamentioning
confidence: 99%
“…A combination of MS imaging and biology experiments showed that this new class of non-surfactant heptapeptides was excreted, promoting motility, and reducing biofilm formation. 28…”
Section: Marine Microorganisms and Phytoplanktonmentioning
confidence: 99%